Correlation and mediation analysis between plasmapheresis donation behavior and bone mineral density and bone metabolism biomarkers: a cross-sectional study based on plasmapheresis donors at high risk of osteoporosis in China - Li,Wan; Liu,Jia; Li,Changqing; Yang,Hui; Yang,Yating; Li,Zhiwei; Yang,Shouqiang; He,Yuan; Xiao,Guanglin; Wang,Ya; Chen,Yongjun (PeerJ, 2024)
Background As a group of more than 3.67 million people, the bone health of Chinese plasmapheresis donors, which the main population is also a risk group of osteoporosis (OP), has raised concerns. Therefore, this article investigates the relationship between bone mineral density (BMD), bone metabolism indicators, and plasmapheresis donation behavior among some high-risk plasmapheresis donors for OP in China, and further explores the mediating factors through reasonable statistical methods. Methods Recruiting long-term and highly active plasmapheresis donors and new donors to measure the total calcium, albumin (ALB), 25-hydroxy vitamin D (25OHD), parathyroid hormone (PTH), type I procollagen amino-terminal peptide (P1NP), and type I collagen carboxy-terminal peptide (β-CTX) and serum ferritin (SF). Then, multiple linear regression was used to adjust confounding factors. Using restrictive cubic splines to explore the nonlinear relationship. Using the Bootstrap method, investigate whether SF has a mediating effect between plasmapheresis donation behavior and bone metabolism biomakers. Finally, analyze the differences in BMD between the two. Results Compared to new donors, repeat donors have a lower 25OHD, β-CTX and SF levels, while P1NP and PTH levels are high, with statistical differences. The Bootstrap analysis results show that SF level is a partial mediating factor between plasmapheresis donation behavior and bone metabolism biomakers, with a mediating effect ratio of 21.8%. There was no significant difference in the BMD between the two. Conclusion Long-term and frequently plasmapheresis donation does not affect the bone mass of even elderly donors at high risk for osteoporosis under the existing collection standards and anticoagulant use in China. However, as a self-regulation way, it does increase the osteogenic activity of the body.
Keywords: Osteoporosis; Plasmapheresis donation; BMD; Ferritin; Vitamin D